Lasītprasmes attīstīšana 10 – 12 gadu vecumā, pilnveidojot koncentrēšanās spējas - Bašķe, Dace (Latvijas Universitāte, 2009)
Darba nosaukums: Lasītprasmes attīstība 10-12 gadu vecumā. Pētījuma mērķis: izzināt lasītprasmes attīstības iespējas 10 – 12 gadu vecumā. Pētījuma teorētiskajā daļā tika analizēta lasīšanas darbības un lasītprasmes jēdzieni, lasītprasmes veidošanās agrīnajā pusaudžu vecumā, kā arī skolas un ģimenes ietekme lasītprasmes veidošanā. Pētījuma praktiskajā daļā tika pētīta lasītprasme 4. un 6. klasē, izzināta vecāku ieinteresētība bērnu lasītprasmes apguvē. Tika veikti novērojumi par skolēnu uzmanību, izpratni un teksta uztveri. Atslēgvārdi: lasīšana, lasītprasme, koncentrēšanās, prasmes un izpratne.

The Title of the Bachelor`s Paper: The Development of Reading skills at the age of 10 – 12. The Aim of The Research : To find out about the possibilities to improve the literacy skills for the 10 – 12 year- old Students. In the theoretical part of the present Bachelor`s paper the author has analysed the definitions and the idea of reading and literacy skills, the formation of the literacy skills in the students` early teens as well as the influence both of the school and the parents in the process of the development of literacy skills. In the practical part the author deals with the research on literacy skills in the 4rd and 6th grades as well as deals with the results of the parental involvement in the development of the reading skills and literacy. The author has done the observation about the students` attention, understanding and the text perception. The key words: reading, literacy, concentration, understanding.
Development of reading skills at the age of 10 – 12 through improvement of the concentration skills
Keywords: Pedagoģija